Takhrij and Syarah Hadith of Chemical: Chemical Content of Olive Oil Which is Beneficial to Health - Azhar, Diazka Jasmine; Anwar, Rosihon (Research Parks Publishing LLC, 2021)
The purpose of this research is to discuss the hadith of the Prophet. about the fruit of Olives. This research method is qualitative through the approach of takhrij and sharah hadith with chemical analysis. The results and discussion of this study were that the olive fruit was already popular during the time of the Prophet, and the content of olives was proven to be beneficial for health and body care in the present. The conclusion of this research is takhrij and syarah hadith of the Prophet. about the fruit of Olives with chemical analysis has benefits for the health of the body.